2012
DOI: 10.1007/s10832-012-9689-4
|View full text |Cite
|
Sign up to set email alerts
|

The variation of Curie temperature and dielectric relaxor behaviour in the nominal (1-x)BaTiO3-xBiAlO3 system

Abstract: BiAlO 3 is a perovskite ferroelectric with a high Curie temperature above 520°C. However, it is difficult to prepare pure perovskite phase by the conventional method. In this experiment, BaTiO 3 has been selected as host to incorporate BiAlO 3 , and the nominal binary system of (1-x)BaTiO 3 -xBiAlO 3 has been investigated with regard to its Curie temperature (T c ) and dielectric relax behaviors. It was found that the pure perovskite phase can be retained below x00.08. However, the value of T c in the system d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Maximum dielectric constant and T m at 1 MHz for the studied compositions are listed in Table , where the T m was found to first increase and then decrease with the increase in BY content, being consistent with the literature . The same phenomena was also reported in BaTiO 3 –(Na 0.5 Bi 0.5 )TiO 3 , BaTiO 3 –BiFeO 3 , and BaTiO 3 –(Na 1/4 Bi 3/4 )(Mg 1/4 Ti 3/4 )O 3 systems, but showing a contrary behavior for BaTiO 3 –BiMeO 3 (Me = Al 3+ , Sc 3+ , (Ni 1/2 Ti 1/2 ) 3+ , (Mg 1/2 Ti 1/2 ) 3+ , (Zn 1/2 Ti 1/2 ) 3+14 ) systems when the doped level is low, which may be associated with the synthesis condition of Bi‐based compounds, such as normal solid‐state reactions or sintering at high temperature and high pressure.…”
Section: Resultssupporting
confidence: 88%
“…Maximum dielectric constant and T m at 1 MHz for the studied compositions are listed in Table , where the T m was found to first increase and then decrease with the increase in BY content, being consistent with the literature . The same phenomena was also reported in BaTiO 3 –(Na 0.5 Bi 0.5 )TiO 3 , BaTiO 3 –BiFeO 3 , and BaTiO 3 –(Na 1/4 Bi 3/4 )(Mg 1/4 Ti 3/4 )O 3 systems, but showing a contrary behavior for BaTiO 3 –BiMeO 3 (Me = Al 3+ , Sc 3+ , (Ni 1/2 Ti 1/2 ) 3+ , (Mg 1/2 Ti 1/2 ) 3+ , (Zn 1/2 Ti 1/2 ) 3+14 ) systems when the doped level is low, which may be associated with the synthesis condition of Bi‐based compounds, such as normal solid‐state reactions or sintering at high temperature and high pressure.…”
Section: Resultssupporting
confidence: 88%
“…Except for BiScO 3 , BiAlO 3 was also taken as end‐member to form solid solutions for capacitor applications. In 2010, our group designed the BaTiO 3 –BiAlO 3 (BT–BA) binary system and investigated its structure description and dielectric behaviours [39, 40]. The temperature‐dependent relative permittivity of 0.9BT–0.1BA composition depicts a typical relaxor behaviour with noticeable frequency dispersion and strongly diffusive and broad dielectric maximum, which suggests the positive effect of BA on BT ceramic for temperature stability.…”
Section: Batio3 ‐Based Materialsmentioning
confidence: 99%
“…The main peaks can be indexed as a typical BaTiO 3 phase structure for all samples types and maintained in the pseudocubic phase. In previous research studies, Huichun 14 and Hou 15 reported that single perovskite phase formation of (1 − x)BT−xBA ceramics can be retained in a low compositional range of 0 ≤ x ≤ 0.08. Such low solubility limits explain the appearance of BaAl 2 O 4 -type secondary phase at 2θ = 28°and 34°(displayed in Figure 4a, b).…”
Section: Resultsmentioning
confidence: 99%